Nucleotide Metabolism Behind Epigenetics - Suganuma, Tamaki; Workman, Jerry L. (Frontiers in Endocrinology, 2021)
The mechanisms of epigenetic gene regulation—histone modifications, chromatin remodeling, DNA methylation, and noncoding RNA—use metabolites as enzymatic cofactors and substrates in reactions that allow chromatin formation, nucleotide biogenesis, transcription, RNA processing, and translation. Gene expression responds to demands from cellular processes that use specific metabolites and alters or maintains cellular metabolic status. However, the roles of metabolites—particularly nucleotides—as regulatory molecules in epigenetic regulation and biological processes remain largely unknown. Here we review the crosstalk between gene expression, nucleotide metabolism, and cellular processes, and explore the role of metabolism in epigenetics as a critical regulator of biological events.